1993
DOI: 10.1038/361473a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 infectivity by zinc-ejecting aromatic C-nitroso compounds

Abstract: Retroviral nucleocapsid and gag-precursor proteins from all known strains of retroviruses contain one or two copies of an invariant sequence, Cys-X2-Cys-X4-His-X4-Cys, that is populated with zinc in mature particles. Modification of cysteine or histidine residues results in defective packaging of genomic viral RNA and formation of non-infectious particles, making these structures potentially attractive targets for antiviral therapy. We recently reported that aromatic C-nitroso ligands of poly(ADP-ribose) polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(165 citation statements)
references
References 34 publications
4
161
0
Order By: Relevance
“…In support of this, preliminary experiments have shown that Ty3 reverse transcription can be inhibited by anti-NCp7 compounds (Rice et al, 1993), raising the possibility that the Ty3 genetic system might be used to screen potential inhibitors of HIV replication.…”
Section: Discussionmentioning
confidence: 93%
“…In support of this, preliminary experiments have shown that Ty3 reverse transcription can be inhibited by anti-NCp7 compounds (Rice et al, 1993), raising the possibility that the Ty3 genetic system might be used to screen potential inhibitors of HIV replication.…”
Section: Discussionmentioning
confidence: 93%
“…These locations are also known to contain calreticulin [5]. Zn z+ plays an important role in the regulation of gene expression, action of some metaloenzymes [1,2], and the capsid formation of human immunodeficiency virus (HIV) [33]. Zn 2+ has also been shown to block Ca 2+ influx in some cells [34] and induce apoptosis in peripheral blood lymphocytes [35].…”
Section: S 1mentioning
confidence: 99%
“…The direct anti-SIV action of NOBA was also assayed with human peripheral lymphocytes that were stimulated by phytohaemagglutinin (PHA-PBL) as described earlier for HIV [6]. This experiment represents a direct comparison between SIV and HIV in the same test system.…”
Section: Resultsmentioning
confidence: 99%
“…pounds, 6-nitroso-l,2-benzopyrone (NOBP) and 3-nitrosobenzamide (NOBA), induce zinc ejection from isolated zinc fingers of p7 or from HIV-1 virions and inhibit HIV-1 replication in human lymphocytes [6]. Since NOBA was more effective in suppressing HIV-1 propagation than NOBP and was well tolerated by uninfected lymphocytes [6], this drug appeared to be the agent of choice for further studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation